2012
DOI: 10.3892/ijo.2012.1399
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside compound K, not Rb1, possesses potential chemopreventive activities in human colorectal cancer

Abstract: Ginsenoside compound K (C-K) is an intestinal microbiota metabolite of ginsenoside Rb1, a major constituent in American ginseng. However, previous ginseng anticancer observations were largely focused on ginseng parent compounds but not metabolites, and anti-colorectal cancer studies on C-K were limited. This study investigated the antiproliferative effects of C-K when compared to those of Rb1, and the related mechanisms of action, in HCT-116 and SW-480 colorectal cancer cells. The effects of Rb1 and C-K on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…Metabolic profiles of ginseng by enteric microbiota have been reported in animals [12, 13], and the actions of selected biotransformed metabolites have been elucidated [14]. For example, compound K, a major metabolite in the protopanaxadiols group, has a better bioactivity than its parent compound, ginsenoside Rb 1 [15]. In an in vitro study we observed that human enteric microbiota metabolized ginseng parent compounds into 25 metabolites [16].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic profiles of ginseng by enteric microbiota have been reported in animals [12, 13], and the actions of selected biotransformed metabolites have been elucidated [14]. For example, compound K, a major metabolite in the protopanaxadiols group, has a better bioactivity than its parent compound, ginsenoside Rb 1 [15]. In an in vitro study we observed that human enteric microbiota metabolized ginseng parent compounds into 25 metabolites [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also observed in our recent ginsenoside studies. [13,17,24] Our data demonstrated that deglycosylation is a promising approach to increase S. baicalensis glycosides’ anticancer potential.…”
Section: Discussionmentioning
confidence: 79%
“…After treatment for 24 h, cell lysates were collected and expression levels of caspases 3, 8, and 9 were determined by ELISA analysis. [13] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed that after oral administration, parent ginseng compounds were biotransformed by the enteric microbiome to metabolites such as Rg3, Rh1, CK and PPD (16, 17). We have also shown that these ginseng metabolites have potential anticancer effects on CRC (31-33). In this study, we evaluated the effects of oral American ginseng on AOM/DSS-induced colitis and colorectal carcinogenesis, and the subsequent changes in metabolomics and gut microbiota profiles.…”
Section: Discussionmentioning
confidence: 84%